2009
DOI: 10.1158/0008-5472.can-09-1499
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Repression of microRNA-129-2 Leads to Overexpression of SOX4 Oncogene in Endometrial Cancer

Abstract: Genetic amplification, mutation, and translocation are known to play a causal role in the upregulation of an oncogene in cancer cells. Here, we report an emerging role of microRNA, the epigenetic deregulation of which may also lead to this oncogenic activation. SOX4, an oncogene belonging to the SRY-related high mobility group box family, was found to be overexpressed (P < 0.005) in endometrial tumors (n = 74) compared with uninvolved controls (n = 20). This gene is computationally predicted to be the target o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
225
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(233 citation statements)
references
References 33 publications
(40 reference statements)
6
225
2
Order By: Relevance
“…The motifs we found hint at proteins involved at ERα/chromatin interactions at differential ERα-binding sites in endometrial tumors of tamoxifen users and nonusers. These motifs indicate a role for stem cell markers, such as SOX4 (39) and NANOG (40) in nonusers, and for members of the nuclear receptor family, including the androgen receptor, glucocorticoid, and thyroid hormone receptor in tamoxifen users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motifs we found hint at proteins involved at ERα/chromatin interactions at differential ERα-binding sites in endometrial tumors of tamoxifen users and nonusers. These motifs indicate a role for stem cell markers, such as SOX4 (39) and NANOG (40) in nonusers, and for members of the nuclear receptor family, including the androgen receptor, glucocorticoid, and thyroid hormone receptor in tamoxifen users.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, ERα-binding sites enriched in endometrial tumors from nonusers mostly included motifs of the forkhead domain family and the high-mobility Box family group. This last group contains well-known stem cell markers, such as sex-determining region Y-box 4 (SOX4) and Nanog homeobox (NANOG), which associate with endometrial cancer (39,40). Both groups contained motifs for leucine zipper proteins at the differential ERα-binding sites.…”
Section: Differential Erα-binding Sites In Tumors From Tamoxifen Usermentioning
confidence: 99%
“…[14][15][16] This may reflect a heterogeneity of tumor samples and the use of different platforms for miRNA detection may account for the differing results. 17 In spite of some discordance, however, 15,16 some common dysregulated miRNAs have been revealed. Dysregulation of miR-182, miR-204, miR-205 and miR-449 identified here is consistent with Wu's report.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas DNA hypomethylation may contribute to the tumorigenic process by inducing chromosomal instability and reactivation of transposons and oncogenes, hypermethylation of CpG islands may result in the silencing of tumor-suppressor genes, a hallmark during cancer onset and progression (Feinberg and Vogelstein, 1983;Gama-Sosa et al, 1983;Fraga and Esteller, 2005;Weber et al, 2005). More recently, changes in the methylation pattern of DNA regions coding for micro-RNAs (miRs) that modulate the expression of oncogenes or tumor suppressors have been reported (Datta et al, 2008;Huang et al, 2009;Pallasch et al, 2009). Inversely, it has been observed that oncofusion proteins can epigenetically silence miRs that are critically involved in lineage specification (Fazi et al, 2007).…”
Section: Current Therapeutic Paradigms To Treat Cancermentioning
confidence: 99%